Sustainability Disclosure and Return on Assets: An Analysis of LQ45 from 2020 to 2022 - Srikalimah, Srikalimah; Munir, Miftahul (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
This research tries to link Return On Assets (ROA) with Sustainable Reporting. Starting from a company's sustainable report on corporate social responsibility and there are several aspects that must be informed by the company to explain the impact of company activities on the economy, environment and social, this research was conducted with the aim: to measure the influence of Return On Assets with Sustainable Reporting from companies. mining company LQ45 which is listed on the Indonesia Stock Exchange (BEI). Using a purposive sample strategy, the population in this study is Return On Assets of mining businesses registered on the Indonesia Stock Exchange (BEI). Simple linear regression analysis is used to analyze the data.. The variables in this research consist of the independent variable, namely Return On Assets as variable X, and the dependent variable (Y), namely Sustainable Reporting. Based on the results of this research, it is proven that there is no significant influence between the independent variable and the dependent variable. These findings have important implications for the disclosure practices of mining companies, highlighting the need for more transparency in their sustainability re-porting to ensure better environmental and social performance.